Macronutrient deficiency is significantly negatively associated with increased catabolism: a study of UUN in stroke patients - Zalfa Alya Anshari; Fuadiyah Nila Kurniasari; Fajar Ari Nugroho (Poltekkes Kemenkes Bandung, 2026)
Background: Stroke is a major cause of disability and mortality worldwide and is frequently associated with hypercatabolic conditions resulting from metabolic stress and inadequate nutritional intake. This condition accelerates body protein breakdown and may worsen clinical outcomes. Nitrogen balance assessment through Urine Urea Nitrogen (UUN) measurement is a reliable indicator of protein metabolism and the degree of catabolism in hospitalized stroke patients. Objective: This study aimed to analyze the relationship between macronutrient intake deficiency and increased catabolism measured by UUN levels in hospitalized stroke patients. Methods: An analytic observational study with a cross-sectional design was conducted among 67 stroke patients who met the inclusion and exclusion criteria. Macronutrient intake (energy, carbohydrates, protein, and fat) was assessed using a 24-hour dietary recall for three consecutive days, while UUN levels were obtained from 24-hour urine examinations. Bivariate analysis was performed using Pearson correlation tests. Results: The results showed that most patients experienced negative nitrogen balance (95.5%). Significant negative correlations were found between UUN levels and energy intake (r = –0.375; p = 0.002), carbohydrate intake (r = –0.289; p = 0.018), protein intake (r = –0.457; p < 0.001), and fat intake (r = –0.399; p < 0.001). Conclusion: Lower macronutrient intake is associated with increased protein catabolism in stroke patients. Adequate macronutrient intake is essential to maintain nitrogen balance and support recovery in stroke patients.